Inversion of donor-acceptor roles in photoinduced intervalence charge transfers - Aramburu Troselj, Bruno Martín (2019)
Upon MLCT photoexcitation, {(tpy)Ru} becomes the electron acceptor in the mixed valence {(tpy-)RuIII-δ-NC-MII+δ} moiety, reversing its role as the electron donor in the ground-state mixed valence analogue. Photoinduced mixed valence interactions can be tuned to obtain extended lifetimes and higher emission quantum yields, beneficial in supramolecular energy conversion schemes.